Development of Cooperative Learning Model Assisted by Lotto Educative Media to Improve Emotional Social Early Childhood (Journal of Primary Education, 2019)
Emotional social skills need to be owned by early childhood so that it is easy for there to socialize with friends. The purpose of this study is to describe a cooperative learning model for early childhood, describing cooperative learning model design assisted by lotto educational media to improve social-emotional early childhood and describe the final model of the effectiveness of cooperative learning development models assisted by lotto educational media to improve social-emotional early childhood. The research method used is research and development research. Data analysis techniques using paired sample t-test and independent sample t-test. The research subjects were teachers, and kindergarten students aged 5-6 years. The instrument is based on the level of achievement of social emotional development in early childhood. The results of the observations show that when learning in the classroom, teachers still rarely apply cooperative-based learning that can improve socialization activities among students. The results of this model are useful and practical for improving social-emotional early childhood. The children's social-emotional improvement in the experimental class and the social-emotional average of the experimental class children were better than the control class. The benefits of this study can add information and knowledge to the broader community and early childhood about cooperative learning models assisted by lotto educational media to improve social-emotional early childhood.